The new Cambridge companion to Jesus - Bockmuehl, Markus 1961- (Cambridge, United Kingdom New York, NY, USA Port Melbourne, Australia New Delhi, India Singapore Cambridge University Press, 2025)
The New Cambridge Companion to Jesus serves as the most up to date guide and resource for understanding Jesus' multifaceted legacy, enduring impact over time and space, and relevance in today's world. Integrating textual, historical, theological, and cultural perspectives, the essays, specially commissioned for this volume, also offer a fresh and diverse overview of Jesus' significance in contemporary global contexts. Key features include insights into Jesus' life and teachings, his role in different religious traditions, and his influence on art, music, and global cultures. The volume also addresses contemporary issues of poverty, race, and power dynamics, making it especially relevant for today's readers. The Companion offers adiversity of perspectives from which to approach the unique identity and importance of Jesus beyond the 2020s, whether in relation to Christianity's cultural and existential crises in the Americas, its precipitous decline in Western Europe, or its unprecedented growth and proliferation in Africa and Asia
Introduction; Part I. Origins: 1. Life and aims of Jesus Dale C. Allison, Jr.; 2. Jesus's religion, praxis and experience of God Volker Leppin; 3. Jesus in the fourfold gospel J. Tyler Brown and Nathan Eubank; 4. Paul's Jesus as the Christ Matthew Novenson; 5. The risen Jesus Markus Bockmuehl; 6. Jesus and the triune God Lewis Ayres; 7. Jesus in the scriptures of Israel Jennie Grillo; Part II. The Diversity of Reception: 8. The apocryphal Jesus Jacob A. Rodriguez; 9. The Islamic Jesus Nicolai Sinai; 10. Jesus in Christian material culture Jeremiah Coogan; 11. Jesus in art and music Robin Jensen and Jeremy Begbie; 12. Jesus in the story of spirituality and worship Volker Leppin; Part III. Ethics, Theology and Critical Scholarship: 13. Jesus in Christian discipleship and ethics Rebekah Eklund; 14. ThebodyofJesusinhispeople Thomas Joseph White, OP; 15. The Church's Jesus in modern theology Emmanuel Durand, OP; 16. The history of Jesus in biblical scholarship James Carleton Paget; IV. The Global Jesus Today: 17. The Jewish Jesus, in Christian and in Jewish memory Barbara U. Meyer; 18. The racial Jesus Jonathan Tran; 19. Jesus, power and the global poor Carlos Raúl Sosa Siliezar and Aruthuckal Varughese John; 20. The Asian faces of Jesus K. K. Yeo; 21. Jesus of Africa Diane B. Stinton and Victor I. Ezigbo; Part V. Outlook: 22. The future of Jesus of Nazareth: Yesterday, today, and tomorrow C. Kavin Rowe.
Zielgruppe: 5PGM, Bezug zu Christen und christlichen Gruppen
Literaturverzeichnis: Seite 379-399
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Jesus Christ -- Biography; Jesus Christ -- History of doctrines; 21. Jahrhundert (ca. 2000 bis ca. 2100); 21st Century; BCE to c 500 CE; ca. 1 bis ca. 500 n. Chr; 21st century history: from c 2000 -; BIB000000; Christentum: Heilige Texte und geheiligte Schriften; Christian leaders & leadership; Christian Theology; Christianity; General & world history; Geschichte allgemein und Weltgeschichte; Geschichte der Religion; HISTORY / World; History of religion; Neues Testament; New Testaments; RELIGION / Christian Church / Leadership; RELIGION / Christian Theology / General; Religion / Christianity / History; Biographies; Aufsatzsammlung